2001
DOI: 10.1007/s007010170138
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of Norepinephrine Levels in Plasma and CSF of Patients After Traumatic Brain Injury in Relation to Disruption of the Blood-Brain Barrier

Abstract: Exogenous administration of NE seems to increase NE levels in plasma and CSF. However, in this group of patients with severe TBI there was no clinical evidence that exogenous administration of NE was detrimental to the traumatized patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 0 publications
0
19
0
1
Order By: Relevance
“…Low dose ethanol inhibition of N-methyl-D-aspartate (NMDA) receptors could be neuroprotective as potassium and calcium influx through NMDA receptor channels following TBI leads to neuronal excitotoxicity [9][10][11][12][13]. The systemic catecholamine surge following TBI which is associated with worse outcomes has been shown to be moderated by ethanol [14][15][16]. Aquaporin-4, implicated in the development of cerebral oedema following TBI, has also been shown to be suppressed by ethanol [17].…”
Section: Introductionmentioning
confidence: 95%
“…Low dose ethanol inhibition of N-methyl-D-aspartate (NMDA) receptors could be neuroprotective as potassium and calcium influx through NMDA receptor channels following TBI leads to neuronal excitotoxicity [9][10][11][12][13]. The systemic catecholamine surge following TBI which is associated with worse outcomes has been shown to be moderated by ethanol [14][15][16]. Aquaporin-4, implicated in the development of cerebral oedema following TBI, has also been shown to be suppressed by ethanol [17].…”
Section: Introductionmentioning
confidence: 95%
“…The largest group of papers have looked at catecholamines without consideration of a diagnosis of PSH at all. (15)(16)(17)(18)(19)(20)(21) A similar situation occurs in literature on the effect of TBI on adrenocorticotropic hormone (ACTH)/cortisol levels which have been reported without reference to the occurrence of PSH. (19,(22)(23)(24) Only three single case studies have evaluated catecholamines in the context of PSH.…”
Section: Introductionmentioning
confidence: 70%
“…Following the provision of informed consent (from the patient or their legal representative), consecutive admissions >14 years of age admitted to ICU following severe TBI (21) were assessed over an 18 month period. Subjects were excluded if they were receiving any of the following: 1) NE infusion at doses >0.5 micrograms/kg/min and/or dopamine (D) at doses of >5 micrograms/kg/min; 2) systemic glucocorticoids before or during the ICU admission; 3) thyroid replacement or inhibitor drugs.…”
Section: Data Collectionmentioning
confidence: 99%
“…One study in cats found spikes in NE following TBI (Rosner et al, 1984) as depicted in Figure 2. Clinically, TBI survivors often receive NE therapy for its vasopressive effects and one study found that NE levels in the CSF and plasma were elevated in TBI survivors treated with NE as well as some individuals who did not receive therapeutic NE; interestingly, the spike in plasma levels was independent of whether or not the blood-brain-barrier remained intact (Mautes et al, 2001). In this study, no evidence of toxicity from NE therapy was reported, nor were there correlations between GCS and NE levels.…”
Section: Norepinephrinementioning
confidence: 99%